WATER CONFWATER CONFLICTS: THE CASE OF THE NILE RIVER AND THE GRAND ETHIOPIAN RENAISSANCE DAMLICTS: THE CASE OF THE NILE RIVER AND THE GRAND ETHIOPIAN RENAISSANCE DAM - BADEA, Cătălin (Studia Universitatis Babes-Bolyai Studia Europaea, 2020)
The most crucial element of every life form on our planet, water has always been a source of potential animosity between clans, tribes and even states. With the advent of modern technology we have devoted less and less of our attention to this all-needed resource, but pollution, large-scale industrialization and agriculture, the population boom of the last centuries and crucially the climate calamity that it threatens to unleash, forces us to reconsider the key role played by water in the delicate and fragile ecosystem of our planet. This article takes a look at how water is, and will increasingly be, a source of contention and even conflicts between states, as climate changes and increasingly larger populations will be forced to fight over more and more depleted resources. With a focus on the case of the Nile river and the potential conflict over its water resources between Egypt and Ethiopia, this article examines how the mainstream state of water conflict thinking fails to explain the case of the Nile River Basis and the newly built Grand Ethiopian Renaissance Dam (GERD) and why the alternative ideas that are based on the notions of cooperation and justice might ultimately provide a better way of understanding the complex problem of the delicate management and use of water resources.